A randomised placebo-controlled trial of topical steroid in presumed viral conjunctivitis. Issue 9 (20th January 2011) - Wilkins, Mark R; Khan, Sharmina; Bunce, Catey; Khawaja, Anthony; Siriwardena, Dilani; Larkin, Daniel F P
Abstract : Aims: To assess whether topical steroids improve patient comfort compared with hypromellose in acute presumed viral conjunctivitis. Methods: Patients presenting with acute follicular conjunctivitis, presumed viral in origin, were randomised to receive either dexamethasone 0.1% or hypromellose 0.3% drops four times daily for 1 week. At review after 5–7 days patients completed questionnaires on whether they thought the treatment had helped and on their level of discomfort. A physician assessed conjunctival hyperaemia using a grading scale. Results: 111 patients were randomised: 56 received dexamethasone drops and 55 received hypromellose lubricant drops. Eighty-eight returned for review. Most patients (39/45 (87%)) receiving dexamethasone and most of those receiving hypromellose 30/43 (70%) felt that the treatment helped. Analysis of all responses showed a significant difference between treatments (p=0.0248, rank sum test). No significant differences between dexamethasone and hypromellose arms were found in the patients' perceived level of discomfort or the physician grading of conjunctival hyperaemia. No patient experienced a serious complication. Conclusions: There us now evidence to support the use of a short course of topical dexamethasone for patients presenting with acute follicular conjunctivitis presumed to be viral in origin. Where topical dexamethasone is prescribed we have not found it to be harmful. Trial registration: http://www.controlled-trials.com/ISRCTN50728656 .